Aluminum salt lithium adsorbent, method for preparing the same, and use thereof
Patent Information
- Application Number
- CN202411294247.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2044-09-14
AI Technical Summary
但造粒后吸附剂应用于实际盐湖卤水中的性能会降低,因为粘接剂或聚合物本身对吸附剂粉末仅是物理缠绕或弱的分子间作用力、氢键相互作用等,会导致循环使用过程中出现颗粒的破损及溶胀导致吸附有效成分脱落的情况
[0037]本发明具有以下有益效果:本发明提供的铝盐锂吸附剂在铝盐吸附剂粉末上接枝有功能硅烷偶联剂,制备过程中先利用含乙烯基的硅烷偶联剂对铝盐锂吸附剂材料进行改性得到乙烯基改性铝盐锂吸附剂,将乙烯基改性铝盐锂吸附剂、带亲水基团的硅烷偶联剂、交联剂和巯基化合物混合反应,巯基化合物中含有羧基,带有的羧基负电荷官能团与卤水中的阴离子产生排斥作用,防止溶液中的高价阴离子对铝盐锂吸附剂的堵塞,避免了其“中毒”,还能够增加其亲水性能;含亲水基团的硅烷偶联剂进一步增加其亲水性能,可避免吸附性能的损失。本发明实施例所提供的铝盐锂吸附剂具有较好稳定性能,稳定性能包括造粒成型吸附剂颗粒的强度高,降低粉末吸附剂的溶损率,同时得到多孔高亲水性的内部结构并保证其循环稳定性。
Smart Images

Figure CN119140065B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium extraction technology from salt lakes, and more specifically, to an aluminum salt lithium adsorbent, its preparation method, and its application. Background Technology
[0002] With the widespread application of electronic products and the rapid development of new energy vehicles, the demand for lithium resources has increased significantly. It is predicted that by 2030, a very large lithium demand gap will emerge globally, with a severe shortage in supply. Global lithium resources can be divided into two main categories: salt lake resources and mineral resources, with salt lakes accounting for over 70% of lithium reserves. Extracting lithium from salt lake brines has become an important direction for lithium resource production. To date, various methods have been used to extract lithium from salt lake brines, such as precipitation, extraction, membrane separation, calcination leaching, and adsorption. Among these, adsorption is considered one of the most promising technologies for lithium extraction from salt lake brines due to its cost-effectiveness and environmental friendliness. High-performance adsorbents are a key factor in the efficient lithium extraction of adsorption methods.
[0003] Currently, the adsorbents produced are classified into manganese-based, titanium-based, and aluminum-based adsorbents, and all are in powder form. Most powdered adsorbents suffer powder loss during recycling, limiting their industrial applications. Manganese-based and titanium-based adsorbents require acid for lithium insertion / extraction, further increasing adsorbent loss. In contrast, aluminum-based adsorbents can perform lithium insertion / extraction without acid and exhibit no elution damage, making them a more suitable adsorbent for lithium extraction from salt lakes.
[0004] Improving the morphology of powdered adsorbents through granulation, film formation, foaming, and membrane electrode assembly (MEA) methods can effectively prevent powder loss and increase the recyclability of adsorbents. Among these methods, granulation is the simplest and most commonly used. Granulation typically involves directly mixing the adsorbent powder precursor with a binder, or repeatedly molding the precursor in a polymer solution through a multi-step cross-linking reaction to obtain granular adsorbents. However, the performance of granulated adsorbents in actual salt lake brine is reduced because the binder or polymer itself only physically entangles the adsorbent powder or has weak intermolecular forces and hydrogen bonding interactions, leading to particle breakage and swelling during recycling, resulting in the loss of adsorbent active ingredients. Furthermore, granulation requires complex processes to prepare high-performance adsorbent particles.
[0005] Therefore, there is an urgent need to improve the preparation process of aluminum salt adsorbents in order to enhance the cycle stability of aluminum-based adsorbents and reduce the solubility loss rate of powdered adsorbents.
[0006] In view of this, the present invention is proposed. Summary of the Invention
[0007] The purpose of this invention is to provide an aluminum salt lithium adsorbent, its preparation method and application, which aims to improve the cycle stability of aluminum-based adsorbents while reducing the solubility loss rate of powdered adsorbents.
[0008] This invention is implemented as follows:
[0009] In a first aspect, the present invention provides an aluminum salt lithium adsorbent, comprising aluminum salt adsorbent powder, wherein a functional silane coupling agent is grafted onto the aluminum salt adsorbent powder.
[0010] The preparation process of the lithium aluminum salt adsorbent includes: modifying the lithium aluminum salt adsorbent material with a vinyl-containing silane coupling agent to obtain a vinyl-modified lithium aluminum salt adsorbent; and mixing and reacting the vinyl-modified lithium aluminum salt adsorbent, a silane coupling agent with a hydrophilic group, a crosslinking agent, and a thiol compound.
[0011] Thiol compounds contain a carboxyl group; the hydrophilic group is selected from at least one of amino, hydroxyl and epoxy groups.
[0012] In an optional embodiment, the mass percentage of carboxyl groups in the aluminum salt lithium adsorbent is 10%-40%.
[0013] In an optional embodiment, the aluminum salt lithium adsorbent material is selected from at least one of LiCl·Al(OH)3·nH2O and Li2SO4·Al(OH)3·nH2O;
[0014] Preferably, the vinyl-containing silane coupling agent is selected from at least one of triethoxyvinylsilane, triacetoxyvinylsilane, methylvinyldimethoxysilane, vinyltrimethoxysilane, and allyltrimethoxysilane.
[0015] In an optional embodiment, the thiol compound is selected from at least one of 3-mercaptopropionic acid, mercaptosuccinic acid, 2-mercaptopropionic acid, 6-mercaptohexanoic acid, 12-mercaptododecanoic acid, 11-mercaptoundecanoic acid, and 12-mercaptododecylphosphonic acid.
[0016] Preferably, the silane coupling agent with a hydrophilic group is selected from at least one of 3-piperazinylpropylmethyldimethoxysilane, 3-(2-aminoethylamino)propylmethyldimethylsilane, (3-aminopropyl)triethoxysilane, trimethoxysilane propionate, (3-glycidylpropoxy)trimethoxysilane, and 3-mercaptopropylmethyldimethoxysilane;
[0017] Preferably, the crosslinking agent is selected from at least one of 1,2-bis(triethoxysilyl)ethane and 1,2-bis(triethoxysilyl)ethane.
[0018] In a second aspect, the present invention provides a method for preparing any of the aforementioned embodiments of the lithium aluminum salt adsorbent, comprising: modifying the lithium aluminum salt adsorbent material with a vinyl-containing silane coupling agent to obtain a vinyl-modified lithium aluminum salt adsorbent, and mixing and reacting the vinyl-modified lithium aluminum salt adsorbent, a silane coupling agent with a hydrophilic group, a crosslinking agent, and a thiol compound.
[0019] In an optional embodiment, the preparation process of the vinyl-modified aluminum salt lithium adsorbent includes: mixing and reacting the aluminum salt lithium adsorbent material, the vinyl-containing silane coupling agent and the first solvent, controlling the reaction temperature at 60℃-90℃ and the reaction time at 8h-24h.
[0020] Preferably, a vinyl silane coupling agent containing vinyl groups is first mixed with a first solvent to obtain a vinyl silane coupling agent solution, and then the aluminum salt lithium adsorbent material and the vinyl silane coupling agent solution are mixed and reacted, controlling the mass fraction of the vinyl silane coupling agent solution to be 1%-12%.
[0021] Preferably, the mass ratio of the aluminum salt lithium adsorbent material to the vinyl-containing silane coupling agent is 1:(0.1-0.4);
[0022] Preferably, the particle size of the aluminum salt lithium adsorbent material is 200 mesh-1200 mesh;
[0023] Preferably, the first solvent is a mixture of water and a first organic solvent, wherein the mass fraction of water in the first solvent is 5%-20%; more preferably, the first organic solvent is selected from at least one of anhydrous ethanol, methanol, isopropanol, propanol, glycerol, N-methylpyrrolidone and dimethyl sulfoxide.
[0024] In an optional embodiment, the preparation process of the vinyl-modified aluminum salt lithium adsorbent further includes: after the aluminum salt lithium adsorbent material and the vinyl-containing silane coupling agent have reacted, solid-liquid separation is performed to obtain solid material, and the solid material is washed and dried.
[0025] In an optional embodiment, a vinyl-modified aluminum salt lithium adsorbent, a second solvent, a mercapto compound, a crosslinking agent, and a silane coupling agent with hydrophilic groups are mixed and reacted, with the reaction temperature controlled at 60°C-90°C and the reaction time at 12h-24h.
[0026] Preferably, the mass ratio of the vinyl-modified aluminum salt lithium adsorbent to the thiol compound is 1:(0.05-0.2);
[0027] Preferably, the initiator is selected from at least one of azobisisobutyronitrile and benzoyl peroxide, and the mass ratio of the initiator to the thiol compound is (0.5-2.0):100;
[0028] Preferably, the mass ratio of vinyl-modified aluminum salt lithium adsorbent to crosslinking agent is 1:(0.1-0.4);
[0029] Preferably, the mass ratio of the vinyl-modified aluminum salt lithium adsorbent to the silane coupling agent with hydrophilic groups is 1:(0.1-0.4).
[0030] In an optional embodiment, the vinyl-modified aluminum salt lithium adsorbent is mixed with the second solvent, and then mixed with a mercapto compound, a crosslinking agent, a silane coupling agent with a hydrophilic group, and an initiator, and then heated to react.
[0031] Preferably, the second solvent is a mixture of water and a second organic solvent, wherein the mass fraction of water in the second solvent is 5%-20%; more preferably, the second organic solvent is selected from at least one of anhydrous ethanol, methanol, isopropanol, propanol, glycerol, N-methylpyrrolidone and dimethyl sulfoxide.
[0032] Preferably, after the reaction of the vinyl-modified aluminum salt lithium adsorbent, the mercapto compound, and the silane coupling agent with hydrophilic groups is completed, the mixture is stirred for 2-6 hours before extrusion molding, followed by activation.
[0033] More preferably, activation includes: drying the shaped material;
[0034] Alternatively, activation may involve immersing the shaped material in a solvent and then drying it.
[0035] Thirdly, the present invention provides a method for extracting lithium from salt lake brine, wherein the lithium-containing brine is adsorbed using any of the aluminum salt lithium adsorbents in the foregoing embodiments or the aluminum salt lithium adsorbents prepared by any of the preparation methods in the foregoing embodiments.
[0036] Preferably, after adsorption is complete, lithium is desorbed with water to obtain lithium-delithiated aluminum salt adsorbent particles.
[0037] The present invention has the following beneficial effects: The aluminum-lithium adsorbent provided by the present invention has a functional silane coupling agent grafted onto the aluminum-lithium adsorbent powder. In the preparation process, the aluminum-lithium adsorbent material is first modified with a vinyl-containing silane coupling agent to obtain a vinyl-modified aluminum-lithium adsorbent. The vinyl-modified aluminum-lithium adsorbent, a silane coupling agent with hydrophilic groups, a crosslinking agent, and a thiol compound are mixed and reacted. The thiol compound contains carboxyl groups, and the negatively charged functional groups of the carboxyl groups repel the anions in the brine, preventing the high-valence anions in the solution from clogging the aluminum-lithium adsorbent and avoiding its "poisoning," while also increasing its hydrophilicity. The silane coupling agent with hydrophilic groups further increases its hydrophilicity, which can avoid the loss of adsorption performance. The aluminum-lithium adsorbent provided by the embodiments of the present invention has good stability performance, including high strength of the granulated adsorbent particles, reduced solubility of the powder adsorbent, and a porous, highly hydrophilic internal structure while ensuring its cycle stability.
[0038] During the preparation process, the covalent bonding of the crosslinking agent improves the strength between the molded particles, avoids dissolution, and gives them a three-dimensional spatial structure. Compared with the traditional "film-coating" process of adding binders, the aluminum salt lithium adsorbent provided in this embodiment of the invention does not cause deactivation of adsorption sites, thereby improving cycle stability. Attached Figure Description
[0039] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0040] Figure 1 A process flow diagram of the preparation method of the aluminum salt lithium adsorbent provided in the embodiments of the present invention. Detailed Implementation
[0041] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0042] This invention provides a method for preparing an aluminum salt lithium adsorbent, through... Figure 1 The preparation method for hydrophilic three-dimensional network porous aluminum salt lithium adsorbent includes the following steps:
[0043] S1. Preparation of vinyl-modified aluminum salt lithium adsorbent
[0044] Vinyl-modified lithium aluminum salt adsorbents are obtained by modifying lithium aluminum salt adsorbent materials with vinyl-containing silane coupling agents. The vinyl-containing silane coupling agent is combined with the lithium aluminum salt adsorbent powder material. The vinyl-containing silane coupling agent acts as a "molecular bridge" to facilitate the introduction of other groups in subsequent polymerization.
[0045] In some embodiments, the preparation process of the vinyl-modified aluminum salt lithium adsorbent includes: mixing and reacting the aluminum salt lithium adsorbent material, the vinyl-containing silane coupling agent, and the first solvent at a reaction temperature of 60°C-90°C for 6 hours-24 hours. The reaction is ensured to proceed fully by adjusting the temperature and time.
[0046] Specifically, the reaction temperature of the aluminum salt lithium adsorbent powder material and the vinyl-containing silane coupling agent can be 60℃, 70℃, 80℃, 90℃, etc., and the reaction time can be 6h, 10h, 16h, 20h, 24h, etc.
[0047] In some embodiments, the lithium aluminum salt adsorbent material is selected from at least one of LiCl·Al(OH)3·nH2O and Li2SO4·Al(OH)3·nH2O. The lithium aluminum salt adsorbent material can be any one or a mixture of the above two materials. All of the above lithium aluminum salt adsorbent materials are self-synthesized materials.
[0048] Specifically, the preparation process of LiCl·Al(OH)3·nH2O is referenced in: Zhang Wending, "Synthesis and Performance Study of Lithium Aluminum Salt Adsorbents" [D].
[0049] Specifically, the preparation process of Li2SO4·Al(OH)3·nH2O is referenced in: Liu X, Zhong M, Chen X, et al. Enriching lithium and separating lithium to magnesium from sulfate typesalt lake brine-ScienceDirect[J].2020.105247-105264.
[0050] Furthermore, the particle size of the lithium aluminum salt adsorbent material is 200-1200 mesh, such as 200 mesh, 600 mesh, 900 mesh, 1200 mesh, etc. The lithium aluminum salt adsorbent powder material can be pulverized as needed to prevent the particle size from being too large, which would affect its sufficient contact with the vinyl silane coupling agent.
[0051] In some embodiments, the vinyl-containing silane coupling agent is selected from at least one of triethoxyvinylsilane, triacetoxyvinylsilane, methylvinyldimethoxysilane, vinyltrimethoxysilane, and allyltrimethoxysilane. The vinyl-containing silane coupling agent can be any one or more of the above, all of which can achieve modification of aluminum salt lithium adsorbent materials.
[0052] Furthermore, the mass ratio of the lithium aluminum salt adsorbent material to the vinyl-containing silane coupling agent is controlled at 1:(0.1-0.4), such as 1:0.1, 1:0.2, 1:0.3, 1:0.4, etc. By adjusting the mass ratio of the lithium aluminum salt adsorbent material to the vinyl-containing silane coupling agent, the amount of vinyl groups introduced is controlled, thereby controlling the amount of thiol compounds introduced.
[0053] In practical operation, the vinyl-containing silane coupling agent and the first solvent are first mixed evenly to obtain a vinyl silane coupling agent solution. Then, the aluminum salt lithium adsorbent material is added to the vinyl silane coupling agent solution, stirred and dispersed thoroughly, and the reaction is carried out at a high temperature. By adjusting the amount of the first solvent, the mass fraction of the vinyl silane coupling agent solution can be controlled to be 1%-12%, such as 1wt%, 2wt%, 4wt%, 8wt%, 10wt%, 12wt%, etc. Under this concentration condition, suitable vinyl groups can be grafted onto the aluminum salt lithium adsorbent powder.
[0054] Furthermore, the first solvent is a mixture of water and a first organic solvent, wherein the mass fraction of water in the first solvent is 5%-20%, such as 5%, 10%, 15%, 20%, etc. Within this concentration range, it can promote the complete hydrolysis of the vinyl-containing silane coupling agent, allowing the vinyl-containing silane coupling agent to react fully.
[0055] In some embodiments, the first organic solvent is selected from at least one of anhydrous ethanol, methanol, isopropanol, propanol, glycerol, N-methylpyrrolidone, and dimethyl sulfoxide, and the first organic solvent can be any one or more of the above.
[0056] It should be noted that during the reaction, since the solvent is a mixture of water and organic solvent, it is conducive to the hydrolysis of the vinyl silane coupling agent. The vinyl silane coupling agent has highly reactive hydroxyl groups, which can undergo dehydration condensation reaction with the hydroxyl groups on the surface of the aluminum salt lithium adsorbent. The vinyl silane coupling agent acts as a "molecular bridge", which facilitates the subsequent grafting and polymerization of thiol compounds and is beneficial to the construction of a three-dimensional network porous structure.
[0057] In some embodiments, the preparation process of the vinyl-modified lithium aluminum salt adsorbent further includes: after the reaction of the lithium aluminum salt adsorbent material and the vinyl-containing silane coupling agent is completed, solid-liquid separation is performed to obtain a solid material, which is then washed and dried. The solid-liquid separation method is not limited and can include vacuum filtration, centrifugation, spray drying, etc.; the washing method is not limited and can include rinsing or agitation, etc., followed by drying to remove the washing reagent. For example, short-chain organic alcohols (such as anhydrous ethanol) can be used for washing, which can further accelerate the drying process.
[0058] S2. Preparation of hydrophilic three-dimensional network porous aluminum salt lithium adsorbent particles
[0059] The vinyl-modified lithium aluminum salt adsorbent prepared in step S1, a carboxyl-containing thiol compound, a hydrophilic silane coupling agent, and a crosslinking agent are mixed and reacted. The vinyl-containing silane coupling agent is bonded to the lithium aluminum salt adsorbent powder material, acting as a "molecular bridge." The crosslinking agent covalently bonds to the lithium aluminum salt adsorbent powder, forming a three-dimensional porous structure. The silane coupling agent containing hydrophilic functional groups further increases the hydrophilicity of the aluminum-based adsorbent. The thiol compound reacts with the modified lithium aluminum salt adsorbent, further achieving excellent stability.
[0060] In some embodiments, a vinyl-modified lithium aluminum salt adsorbent, a second solvent, a thiol compound, a crosslinking agent, and a silane coupling agent with hydrophilic groups and an initiator are mixed and reacted. During the reaction, the thiol compound and the vinyl functional groups react, and the crosslinking agent and the silane coupling agent with hydrophilic groups are hydrolyzed to produce highly reactive hydroxyl groups, which react with the hydroxyl groups on the surface of the lithium aluminum salt adsorbent to form a hydrophilic three-dimensional network crosslinked structure.
[0061] In some embodiments, the polymerization reaction temperature is controlled at 60℃-90℃, such as 60℃, 70℃, 80℃, 90℃, etc.; the polymerization reaction time is 12h-24h, such as 12h, 14h, 18h, 22h, 24h, etc. The granulation requirements are met by adjusting the reaction time. After granulation and activation, a hydrophilic three-dimensional network porous structure aluminum salt lithium adsorbent particle is prepared.
[0062] In actual operation, the vinyl-modified aluminum salt lithium adsorbent and the second solvent are first mixed, and then mixed with mercapto compound, crosslinking agent, silane coupling agent with hydrophilic group and initiator. The mixture is heated to react. The reaction does not require inert gas protection and must be carried out in an open reaction vessel with oxygen to prevent the self-polymerization of silane coupling agent and crosslinking agent.
[0063] In some embodiments, the second solvent is a mixture of water and a second organic solvent. The second organic solvent is selected from at least one of anhydrous ethanol, methanol, isopropanol, propanol, glycerol, N-methylpyrrolidone, and dimethyl sulfoxide. The second organic solvent can be any one or more of the above. The mass fraction of water in the second solvent is 5%-20%, such as 5%, 10%, 15%, 20%, etc. Controlling the water concentration within the above range allows the silane coupling agent to be more easily hydrolyzed, promoting the reaction; it also allows the vinyl aluminum salt lithium adsorbent powder to be more uniformly dispersed, achieving the requirement of uniform adsorption performance. Within this range, granulation is possible.
[0064] In some embodiments, the thiol compound is selected from at least one of 3-mercaptopropionic acid, mercaptosuccinic acid, 2-mercaptopropionic acid, 6-mercaptohexanoic acid, 12-mercaptododecanoic acid, 11-mercaptoundecanoic acid, and 12-mercaptododecylphosphonic acid. The thiol compound can be any one or more of these. The thiol compound reacts with the vinyl-modified adsorbent to impart a large number of carboxyl groups to its surface. This improves hydrophilicity and also imbues the adsorbent surface with carboxylic acid groups. In brine, these carboxylic acid groups can ionize into negatively charged carboxylic acid ions, which can repel the high-valence anions in the brine, thus improving the cycle stability of the formed adsorbent. The mass ratio of the vinyl-modified aluminum salt lithium adsorbent to the thiol compound is 1:(0.05-0.2), such as 1:0.05, 1:0.08, 1:0.10, 1:0.15, 1:0.20, etc. The quality control of vinyl-modified lithium aluminum salt adsorbent and mercapto compound should be within the above-mentioned range to ensure the stability of the adsorbent and the formation of its three-dimensional porous structure within a relatively safe range for the lithium aluminum salt adsorbent particles.
[0065] In some embodiments, the crosslinking agent is selected from at least one of 1,2-bis(trimethoxysilyl)ethane and 1,2-bis(triethoxysilyl)ethane, and the crosslinking agent can be any one or a mixture of two of the above. The mass ratio of vinyl-modified aluminum salt lithium adsorbent to crosslinking agent is 1:(0.1-0.4), such as 1:0.1, 1:0.2, 1:0.3, 1:0.4, etc. The amount of crosslinking agent used is preferably within the above range, which can promote the polymerization reaction and facilitate powder formation.
[0066] In some embodiments, the silane coupling agent with a hydrophilic group is selected from at least one of 3-piperazinylpropylmethyldimethoxysilane, 3-(2-aminoethylamino)propylmethyldimethylsilane, (3-aminopropyl)triethoxysilane, trimethoxysilane propionate, (3-glycidylpropoxy)trimethoxysilane, and 3-mercaptopropylmethyldimethoxysilane. The hydrophilic silane coupling agent can be any one or more of the above. The mass ratio of the vinyl-modified aluminum salt lithium adsorbent to the hydrophilic silane coupling agent is 1:(0.1-0.4), such as 1:0.1, 1:0.2, 1:0.3, 1:0.4, etc. Using silane coupling agent within the above range is preferable, as it can significantly increase the hydrophilicity of the product.
[0067] In some embodiments, the initiator is selected from at least one of azobisisobutyronitrile (AIBN) and benzoyl peroxide, and the initiator can be any one or a mixture of two of the above. The mass ratio of initiator to mercapto compound is (0.5-2.0):100, such as 0.5:100, 1.0:100, 1.5:100, 2.0:100, etc. The initiator mainly initiates the reaction between vinyl groups and mercapto groups, and the amount of initiator used within the above range can promote the polymerization reaction.
[0068] Furthermore, after the polymerization reaction of the vinyl-modified aluminum salt lithium adsorbent, the thiol compound, and the silane coupling agent with hydrophilic groups is completed, the stirring time is 2-6 hours before it can be used in a molding and granulation machine for molding. Too short a stirring time hinders the reaction, while too long a time makes subsequent molding and granulation difficult. Specifically, the stirring time after the reaction can be 2 hours, 3 hours, 4 hours, 5 hours, or 6 hours. The molding process can be carried out using a granulator or an extrusion-spheronization machine.
[0069] Furthermore, after molding, the material is directly activated. Activation methods include drying or soaking-drying. Soaking can be done using water or organic solvents, while drying removes unreacted solvents and other raw materials, forming a porous structure. The molded particles are cylinders with a diameter of 1 mm or spheres with a diameter of 0.2-2 mm.
[0070] This invention provides an aluminum salt lithium adsorbent, comprising aluminum salt adsorbent powder, on which a functional silane coupling agent is grafted. It can be prepared by the preparation method provided in this invention.
[0071] It should be noted that the thiol compound bound to the vinylsilane coupling agent contains a carboxyl group, which can generate a charge interaction with the anions in the brine, preventing the "poisoning" phenomenon of the lithium aluminum salt adsorbent. Furthermore, this thiol compound, based on the surface of the lithium aluminum salt adsorbent powder material, is beneficial to the formation of its three-dimensional network structure after molding. The formation of the three-dimensional network structure mainly relies on the connecting effect of the cross-linking agent. The lithium aluminum salt adsorbent powder is directly bonded through covalent bonds, and will not adhere to the adsorbent surface to avoid clogging its active sites, thus ensuring the adsorption performance of the adsorbent powder, improving the strength after molding, and increasing the cycle stability of the lithium aluminum salt adsorbent.
[0072] In some embodiments, the mass percentage of carboxyl groups in the aluminum salt lithium adsorbent is 10%-40%, such as 10%, 20%, 30%, 40%, etc.
[0073] It should be noted that the aluminum salt lithium adsorbent provided in the embodiments of the present invention has the following advantages: (1) The traditional adhesive "film bonding" method will lead to the coverage of active adsorption points, the decrease of adsorption performance and the poor cycle stability. The aluminum salt lithium adsorbent powder provided in the embodiments of the present invention is connected by covalent bonds, which constitutes a three-dimensional spatial network porous structure, which has higher strength and better stability; (2) The silane coupling agent containing hydrophilic groups increases its hydrophilicity after molding, increases wettability, and avoids the reduction of adsorption performance; (3) No complicated granulation molding process is required; (4) Its aluminum salt lithium adsorbent contains carboxylic acid groups, which can generate charge interaction with anions in brine, avoiding the "poisoning" of aluminum salt lithium adsorbent.
[0074] This invention provides a method for extracting lithium from salt lake brine. The method utilizes the aluminum-lithium salt adsorbent provided in this invention to adsorb lithium-containing brine. By improving the aluminum-lithium salt adsorbent, the cycle stability of the aluminum-lithium salt adsorbent can be significantly improved.
[0075] After adsorption using the aluminum salt lithium adsorbent provided in this embodiment of the invention, no acid washing is required; lithium can be directly desorbed with water. The delithiated aluminum salt lithium adsorbent particles can be obtained simply by elution with pure water. During adsorption and desorption, its strong hydrophilic properties facilitate lithium-ion exchange within the adsorbent.
[0076] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0077] Example 1
[0078] This embodiment provides a method for preparing an aluminum salt lithium adsorbent, the specific steps of which are as follows:
[0079] (1) Using an aqueous solution containing 93 wt% anhydrous ethanol as a solvent, prepare a silane coupling agent solution of 2 wt% triethoxyvinylsilane. Add LiCl·Al(OH)3·nH2O powder material (also known as aluminum salt lithium adsorbent powder (anion is Cl)). - The aluminum salt lithium adsorbent powder was pulverized to 200 mesh using a high-speed pulverizer. A certain amount of the powder was then fully dispersed in a vinyl silane coupling agent solution and reacted at 60°C for 6 hours. After the reaction, the powder was filtered, washed with anhydrous ethanol, and dried to obtain vinyl-modified aluminum salt lithium adsorbent powder. The mass ratio of the aluminum salt lithium adsorbent powder to the vinyl-containing silane coupling agent was controlled to be 1:0.2.
[0080] (2) Using an aqueous solution containing 93 wt% anhydrous ethanol as a solvent, the vinyl-modified aluminum salt lithium adsorbent obtained in step (1) was mixed with the solvent, and the solid-liquid ratio was controlled to be 1.2 g / mL. 3-mercaptopropionic acid was added to the solution as a mercapto compound, 1,2-bis(trimethoxysilylethane) as a crosslinking agent, 3-piperazinylpropylmethyldimethoxysilane as a silane coupling agent containing hydrophilic groups, and azobisisobutyronitrile as an initiator. The mixture was then heated to 60 °C and reacted for 12 h. After the reaction was completed, the mixture was stirred for 2 h and then extruded and granulated. After drying and activation (drying temperature was 100 °C and drying time was 12 h, the same below), hydrophilic three-dimensional network porous aluminum salt lithium adsorbent particles were obtained. The mass ratio of vinyl-modified lithium aluminum salt adsorbent powder to thiol compound is 1:0.05, the mass of crosslinking agent is 10% of the mass of vinyl-modified lithium aluminum salt adsorbent powder (i.e., the mass ratio of vinyl-modified lithium aluminum salt adsorbent powder to crosslinking agent is 1:0.1), the mass of initiator is 0.5% of the mass of thiol compound, and the mass of silane coupling agent containing hydrophilic groups is 10% of the mass of vinyl-modified lithium aluminum salt adsorbent powder (i.e., the mass ratio of vinyl-modified lithium aluminum salt adsorbent powder to silane coupling agent containing hydrophilic groups is 1:0.1).
[0081] This embodiment also provides a method for lithium extraction from salt lake brine, as follows: Aluminum salt lithium adsorbent particles are placed in an adsorption column containing brine for lithium adsorption. After adsorption, the same volume of pure water is used for elution, completing one cycle of adsorption-elution for the aluminum salt lithium adsorbent particles. This adsorption-elution process is repeated 50 times to determine its cycle stability. The brine composition is as follows: magnesium ions 8.26 g / L, sodium ions 19.25 g / L, lithium ions 1.84 g / L, chloride ions 20.13 g / L, and sulfate ions 40.02 g / L.
[0082] Example 2
[0083] This embodiment provides a method for preparing an aluminum salt lithium adsorbent, the specific steps of which are as follows:
[0084] (1) Using an aqueous solution containing 84 wt% anhydrous methanol as a solvent, a silane coupling agent solution of 8 wt% vinyltrimethoxysilane was prepared. Li₂SO₄·Al(OH)₃·nH₂O powder was pulverized to 600 mesh using a high-speed pulverizer. A certain amount of lithium aluminum salt adsorbent powder was placed in the vinyl silane coupling agent solution and fully dispersed. The mixture was reacted at 70°C for 10 h. After the reaction, the mixture was filtered, washed with anhydrous ethanol, and dried to obtain vinyl-modified lithium aluminum salt adsorbent powder. The mass ratio of lithium aluminum salt adsorbent powder to vinyl-containing silane coupling agent was controlled to be 1:0.3.
[0085] (2) Using an aqueous solution containing 84 wt% anhydrous methanol as the solvent, the vinyl-modified lithium aluminum salt adsorbent obtained in step (1) was mixed with the solvent, and the solid-liquid ratio was controlled at 1.2 g / mL. 2-Mercaptopropionic acid was added to the solution as a mercapto compound, 1,2-bis(triethoxysilyl)ethane as a crosslinking agent, (3-aminopropyl)triethoxysilane as a silane coupling agent with hydrophilic groups, and benzoyl peroxide as an initiator. The mixture was then heated to 70 °C and reacted for 14 h, followed by stirring for 4 h. The mixture was then used for molding, extrusion granulation, drying, and activation to obtain hydrophilic three-dimensional network porous lithium aluminum salt adsorbent particles. The mass ratio of vinyl-modified lithium aluminum salt adsorbent powder to mercapto compound was 1:0.08, the mass of crosslinking agent was 20% of the mass of vinyl-modified lithium aluminum salt adsorbent powder, the mass of initiator was 1% of the mass of mercapto compound, and the mass of silane coupling agent containing hydrophilic groups was 20% of the mass of lithium aluminum salt adsorbent powder.
[0086] This embodiment also provides a method for extracting lithium from salt lake brine, which is the same as that in Embodiment 1.
[0087] Example 3
[0088] This embodiment provides a method for preparing an aluminum salt lithium adsorbent, the specific steps of which are as follows:
[0089] (1) Using an aqueous solution containing 78 wt% isopropanol as a solvent, a 10 wt% allyltrimethoxysilane silane coupling agent solution was prepared. LiCl·Al(OH)3·nH2O powder was pulverized to 900 mesh using a high-speed pulverizer. A certain amount of lithium aluminum salt adsorbent powder was placed in the vinyl silane coupling agent solution and fully dispersed. The mixture was reacted at 80℃ for 16 h. After the reaction, the mixture was filtered, washed with anhydrous isopropanol, and dried to obtain vinyl-modified lithium aluminum salt adsorbent powder. The mass ratio of lithium aluminum salt adsorbent powder to vinyl-containing silane coupling agent was controlled to be 1:0.4.
[0090] (2) Using an aqueous solution containing 78 wt% isopropanol as a solvent, the vinyl-modified lithium aluminum salt adsorbent obtained in step (1) was mixed with the solvent, and the solid-liquid ratio was controlled at 1.2 g / mL. 6-Mercaptohexanoic acid was added to the solution as a mercapto compound, 1,2-bis(trimethoxysilylethane) as a crosslinking agent, trimethoxysilane propionate as a silane coupling agent, and benzoyl peroxide as an initiator. The mixture was then heated to 80°C and reacted for 22 h, followed by stirring for 6 h. The resulting product was then extruded and granulated, dried, and activated to obtain hydrophilic three-dimensional network porous lithium aluminum salt adsorbent particles. The mass ratio of the vinyl-modified lithium aluminum salt adsorbent powder to the mercapto compound was 1:0.15, the mass of the crosslinking agent was 30% of the mass of the vinyl-modified lithium aluminum salt adsorbent powder, the mass of the initiator was 2.0% of the mass of the mercapto compound, and the mass of the silane coupling agent containing hydrophilic groups was 40% of the mass of the lithium aluminum salt adsorbent powder.
[0091] This embodiment also provides a method for extracting lithium from salt lake brine, which is the same as that in Embodiment 1.
[0092] Example 4
[0093] This embodiment provides a method for preparing an aluminum salt lithium adsorbent, the specific steps of which are as follows:
[0094] (1) Using an aqueous solution containing 68 wt% N-methylpyrrolidone as a solvent, a silane coupling agent solution of 12 wt% triacetoxyvinylsilane was prepared. LiCl·Al(OH)3·nH2O powder was pulverized to 1200 mesh using a high-speed pulverizer. A certain amount of lithium aluminum salt adsorbent powder was placed in the vinyl silane coupling agent solution and fully dispersed. The mixture was reacted at 90℃ for 6 h. After the reaction, the mixture was filtered, washed with anhydrous isopropanol, and dried to obtain vinyl-modified lithium aluminum salt adsorbent powder. The mass ratio of lithium aluminum salt adsorbent powder to vinyl-containing silane coupling agent was controlled to be 1:0.2.
[0095] (2) Using an aqueous solution containing 68 wt% N-methylpyrrolidone as a solvent, the vinyl-modified lithium aluminum salt adsorbent obtained in step (1) was mixed with the solvent, and the solid-liquid ratio was controlled at 1.2 g / mL. Mercaptosuccinic acid was added to the solution as a mercapto compound, 1,2-bis(triethoxysilyl)ethane as a crosslinking agent, 3-piperazinylpropylmethyldimethoxysilane as a silane coupling agent, and azobisisobutyronitrile as an initiator. The mixture was then heated to 90°C and reacted for 24 h, followed by stirring for 2 h. The mixture was then extruded and granulated, and after drying and activation, hydrophilic three-dimensional network porous lithium aluminum salt adsorbent particles were obtained. The mass ratio of vinyl-modified lithium aluminum salt adsorbent powder to mercapto compound was 1:0.2, the mass of the crosslinking agent was 40% of the mass of the vinyl-modified lithium aluminum salt adsorbent powder, the mass of the initiator was 2.0% of the mass of the mercapto compound, and the mass of the silane coupling agent containing hydrophilic groups was 40% of the mass of the lithium aluminum salt adsorbent powder.
[0096] This embodiment also provides a method for extracting lithium from salt lake brine, which is the same as that in Embodiment 1.
[0097] Example 5
[0098] The only difference between this embodiment and Embodiment 1 is that the aluminum salt lithium adsorbent powder is a mixed powder of LiCl·Al(OH)3·nH2O and Li2SO4·Al(OH)3·nH2O, with a mass ratio of 1:1.
[0099] Example 6
[0100] The only difference between this embodiment and embodiment 2 is that the reaction time for both steps (1) and (2) is 24 hours.
[0101] Example 7
[0102] The only difference between this embodiment and embodiment 4 is that the modification temperature in step (1) and the polymerization reaction temperature in step (2) are both 60°C.
[0103] Example 8
[0104] The only difference from Example 1 is that in step (1) LiCl·Al(OH) )3 The nH2O powder material was replaced with an equal amount of Li2SO4·Al(OH)3·nH2O powder material.
[0105] Example 9
[0106] The only difference from Example 1 is that the amount of LiCl·Al(OH)3·nH2O powder material used in step (1) is 0.6 times the amount of powder used in Example 1.
[0107] Comparative Example 1
[0108] The only difference between the comparative example and Example 1 is that: Comparative example 1 directly uses aluminum salt lithium adsorbent powder for brine lithium extraction, without any modification or polymerization reaction molding granulation process.
[0109] Comparative Example 2
[0110] Comparative Example 2 is consistent with the preparation process and dosage of step (1) of Example 1. The difference is that no crosslinking agent or hydrophilic silane coupling agent is added in step (2). The product obtained in step (1) is reacted with a mercapto compound (the dosage is consistent with that in step (2)) and then used for granulation.
[0111] Comparative Example 3
[0112] The only difference between Comparative Example 3 and Example 1 is that the aluminum salt lithium adsorbent was granulated using conventional methods. The specific method is as follows: Unmodified aluminum salt lithium adsorbent powder (i.e., LiCl·Al(OH)3·nH2O powder material in Example 1) was taken and mixed with binder polyvinyl chloride (PVC) powder and organic solvent N-methylpyrrolidone at a mass ratio of 1:0.3:0.2, and then granulated using the same extruder.
[0113] Comparative Example 4
[0114] The only difference between Comparative Example 4 and Comparative Example 3 is that: the unmodified aluminum salt lithium adsorbent powder, which is the same as that in Example 1, is mixed with the binder polyvinyl chloride (PVC) powder and the organic solvent N-methylpyrrolidone at a mass ratio of 1:0.4:0.4, and then granulated using the same extruder.
[0115] Comparative Example 5
[0116] The only difference from Example 1 is that no thiol compound is added in step (2).
[0117] Comparative Example 6
[0118] The only difference from Example 1 is that no hydrophilic silane coupling agent is added in step (2).
[0119] Experimental Example 1
[0120] The desorption capacity, desorption capacity retention rate, and hydrophilicity of the adsorbents prepared in the test examples and comparative examples are shown in Table 1.
[0121] Test method:
[0122] (1) Desorption capacity = (volume of eluent * concentration of Li in eluent) / column volume * 0.46 (coefficient of Li in lithium oxide);
[0123] (2) Desorption capacity retention rate = Desorption capacity after 50 cycles / Initial desorption capacity * 100%;
[0124] (3) Solubility test: After the aluminum salt lithium adsorbent powder or granules of the above examples and comparative examples were subjected to 50 adsorption-desorption cycles, the aluminum salt lithium adsorbent powder was taken out, dried and weighed, and the aluminum salt lithium adsorbent granules were dried and weighed. Then the solubility rate of the aluminum salt lithium adsorbent was calculated. The calculation formula is as follows: Solubility rate = m1 / m0*100%, where m1 is the dried weight after 50 cycles and m0 is the initial dried weight.
[0125] (4) Hydrophilicity test: After placing a sufficiently large droplet (50 μL) on the surface of the sample to be tested, record the droplet wetting time until there is no obvious droplet.
[0126] Table 1. Results of adsorption performance, stability, and hydrophilicity tests of the adsorbents in the examples and comparative examples.
[0127]
[0128]
[0129] As can be seen from Table 1, the hydrophilic three-dimensional network porous aluminum salt lithium adsorbent particles prepared in the embodiments of the present invention can significantly improve the stability of the aluminum salt lithium adsorbent particles after brine lithium extraction, including stable adsorption performance, stable cycling, low solubility, and excellent hydrophilicity, while preventing the "poisoning" phenomenon of high-valence anions.
[0130] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing an aluminum salt lithium adsorbent, characterized in that, The preparation process of the aluminum salt lithium adsorbent includes: modifying the aluminum salt lithium adsorbent material with a vinyl-containing silane coupling agent to obtain a vinyl-modified aluminum salt lithium adsorbent; and mixing and reacting the vinyl-modified aluminum salt lithium adsorbent, a silane coupling agent with a hydrophilic group, a crosslinking agent, and a thiol compound. The thiol compound contains a carboxyl group; the hydrophilic group is selected from at least one of amino, hydroxyl, and epoxy groups; The crosslinking agent is selected from at least one of 1,2-bis(triethoxysilyl)ethane and 1,2-bis(triethoxysilyl)ethane; The aluminum salt lithium adsorbent material is selected from at least one of LiCl•Al(OH)3•nH2O and Li2SO4•Al(OH)3•nH2O.
2. The preparation method according to claim 1, characterized in that, In the aluminum salt lithium adsorbent, the mass percentage of carboxyl groups is 10%-40%.
3. The preparation method according to claim 1, characterized in that, The vinyl-containing silane coupling agent is selected from at least one of triethoxyvinylsilane, triacetoxyvinylsilane, methylvinyldimethoxysilane, vinyltrimethoxysilane, and allyltrimethoxysilane.
4. The preparation method according to claim 3, characterized in that, The thiol compound is selected from at least one of 3-mercaptopropionic acid, mercaptosuccinic acid, 2-mercaptopropionic acid, 6-mercaptohexanoic acid, 12-mercaptododecanoic acid, 11-mercaptoundecanoic acid, and 12-mercaptododecylphosphonic acid.
5. The preparation method according to claim 1, characterized in that, The silane coupling agent with a hydrophilic group is selected from at least one of 3-piperazinylpropylmethyldimethoxysilane, (3-aminopropyl)triethoxysilane, trimethoxysilane propionate, (3-glycidylpropoxy)trimethoxysilane, and 3-mercaptopropylmethyldimethoxysilane.
6. The preparation method according to claim 1, characterized in that, The preparation process of the vinyl-modified aluminum salt lithium adsorbent includes: mixing and reacting the aluminum salt lithium adsorbent material, the vinyl-containing silane coupling agent and the first solvent, controlling the reaction temperature at 60℃-90℃ and the reaction time at 8h-24h.
7. The preparation method according to claim 6, characterized in that, First, the vinyl-containing silane coupling agent and the first solvent are mixed to obtain a vinyl silane coupling agent solution. Then, the aluminum salt lithium adsorbent material and the vinyl silane coupling agent solution are mixed and reacted, and the mass fraction of the vinyl silane coupling agent solution is controlled to be 1%-12%.
8. The preparation method according to claim 7, characterized in that, The mass ratio of the aluminum salt lithium adsorbent material to the vinyl-containing silane coupling agent is 1:(0.1-0.4).
9. The preparation method according to claim 8, characterized in that, The particle size of the aluminum salt lithium adsorbent material is 200 mesh to 1200 mesh.
10. The preparation method according to claim 6, characterized in that, The first solvent is a mixture of water and a first organic solvent, wherein the mass fraction of water in the first solvent is 5%-20%.
11. The preparation method according to claim 10, characterized in that, The first organic solvent is selected from at least one of anhydrous ethanol, methanol, isopropanol, propanol, glycerol, N-methylpyrrolidone, and dimethyl sulfoxide.
12. The preparation method according to claim 6, characterized in that, The preparation process of the vinyl-modified aluminum salt lithium adsorbent further includes: after the reaction of the aluminum salt lithium adsorbent material and the vinyl-containing silane coupling agent is completed, solid-liquid separation is performed to obtain solid material, and the solid material is washed and dried.
13. The preparation method according to claim 1, characterized in that, The vinyl-modified aluminum salt lithium adsorbent, the second solvent, the mercapto compound, the crosslinking agent, the hydrophilic silane coupling agent, and the initiator are mixed and reacted, with the reaction temperature controlled at 60℃-90℃ and the reaction time at 12h-24h.
14. The preparation method according to claim 13, characterized in that, The mass ratio of the vinyl-modified aluminum salt lithium adsorbent to the mercapto compound is 1:(0.05-0.2).
15. The preparation method according to claim 13, characterized in that, The initiator is selected from at least one of azobisisobutyronitrile and benzoyl peroxide, and the mass ratio of the initiator to the thiol compound is (0.5-2.0):
100.
16. The preparation method according to claim 13, characterized in that, The mass ratio of the vinyl-modified aluminum salt lithium adsorbent to the crosslinking agent is 1:(0.1-0.4).
17. The preparation method according to claim 13, characterized in that, The mass ratio of the vinyl-modified aluminum salt lithium adsorbent to the silane coupling agent with hydrophilic groups is 1:(0.1-0.4).
18. The preparation method according to claim 13, characterized in that, The vinyl-modified aluminum salt lithium adsorbent is mixed with the second solvent, and then mixed with the mercapto compound, the crosslinking agent, the silane coupling agent with hydrophilic groups, and the initiator, and then heated to react.
19. The preparation method according to claim 18, characterized in that, The second solvent is a mixture of water and a second organic solvent, wherein the mass fraction of water in the second solvent is 5%-20%.
20. The preparation method according to claim 19, characterized in that, The second organic solvent is selected from at least one of anhydrous ethanol, methanol, isopropanol, propanol, glycerol, N-methylpyrrolidone, and dimethyl sulfoxide.
21. The preparation method according to claim 18, characterized in that, After the reaction of the vinyl-modified aluminum salt lithium adsorbent, the mercapto compound, and the silane coupling agent with hydrophilic groups is completed, the mixture is stirred for 2-6 hours before extrusion molding, followed by activation.
22. The preparation method according to claim 21, characterized in that, The activation includes: drying the shaped material; Alternatively, the activation may include: soaking the shaped material in a solvent and then drying it.
23. A method for extracting lithium from salt lake brine, characterized in that, The lithium aluminum salt adsorbent prepared by any one of the preparation methods described in claims 1-22 is used to adsorb lithium-containing brine.
24. The method for lithium extraction from salt lake brine according to claim 23, characterized in that, After adsorption is complete, lithium is desorbed with water to obtain lithium-delithiated aluminum salt adsorbent particles.
Citation Information
Patent Citations
Binder emulsion, preparation method of binder emulsion, coating slurry, lithium ion battery diaphragm and preparation method of lithium ion battery diaphragm
CN120077513A